The history of the government regulation of inLAND waterways before revolution in Russia - T. Gaynochenko; E. Kurbatova (Вестник университета)
The article covers the peculiarities of development of a state management system of tsarist Russian inland water transport. Special attention is paid to the growth of inland shipping, port facilities and to construction projects of river ports. It also gives a description of functions and main activities of transport departments.